Christian engagement with Islam : ecumenical journeys since 1910 - Pratt, Douglas. (Middle East and Islamic Studies E-Books Online, Collection 2017, ISBN: 9789004325999., 2017)
Why did the Christian Church, in the twentieth century, engage in dialogue with Islam? What has been the ecumenical experience? What is happening now? Such questions underlie Douglas Pratt's Christian Engagement with Islam: Ecumenical Journeys since 1910 . Pratt charts recent Christian (WCC and Vatican) engagement with Islam up to the early 21st century and examines the ecumenical initiatives of Africa's PROCMURA, 'Building Bridges', and the German 'Christian-Muslim Theological Forum', together with responses to the 2007 'Common Word' letter. Between them, Islam and Christianity represent over half the earth's population. Their history of interaction, positive and negative, impacts widely still today. Contentious issues remain real enough, yet the story and ongoing reality of contemporary Christian-Muslim engagement is both exciting and encouraging.